IMPLEMENTASI MEDIA ULAR TANGGA UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS KELAS IV SDN 2 PALEMBANG - Kartika, Nadia Dwi; Akhsan, Hamdi; Ribkoh, Ribkoh (Jurnal Dedikasi Pendidikan, 2025)
This study aimed to analyze the effectiveness of using the snakes and ladders game to improve English vocabulary mastery among fourth-grade students at SDN 2 Palembang, as well as to enhance their learning engagement and motivation. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, carried out over two cycles. Data were collected through direct observation of students’ learning activities and vocabulary tests (pre-test and post-test) to measure the improvement in vocabulary. The findings showed a significant improvement in both vocabulary mastery and student engagement. During pre-cycle, students mastered an average of 10 vocabulary words, an average score of 51.3 and an engagement level of 48%. After first cycle, an average number of vocabulary words mastered increased to 26, an average score of 66.3 and an engagement rate of 65%. In second cycle, further improvements were observed, with an average of 37 vocabulary words mastered, an average score of 83.2, and a student engagement level of 93%. Based on these results, it can be concluded the use of snakes and ladders game is effective in enhancing English vocabulary mastery and increasing student engagement in learning.